Virtual humans playing the role of patients in self‐medication consultations : perspectives of undergraduate pharmacy students - Cláudio, Ana Paula (2017)
Poster presented at the GRAPP 2016 - 11th International Conference on Computer Graphics Theory and Application. 27-29 February 2016, Rome